Programa de música “Canta y aprende” para mejorar la atención de las estudiantes de primer grado de Primaria - Trujillo, 2019 - Chuquimiguel Mantilla, Karen Alegria (2021)
This research entitled "Sing and learn" music program to improve the attention of first grade _x000D_ students of primary school - Trujillo, 2019, aimed to improve the level of attention of the _x000D_ students. The experimental design was used. We worked with a sample made up of 21 first grade _x000D_ “F” students from the I.E. n ° 81007 "Modelo", Av. Ejército. The program consisted of 15 _x000D_ workshops. Thus, the results confirm that the implementation of the educational music program _x000D_ "Sing and learn" has significantly improved the level of attention of the students.